SYARIAT MENYUSUI DALAM ALQURAN (Kajian Surat Al-Baqarah Ayat 233) - Ismail, Hidayatullah (At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2018)
This article talks about the ordering of breastfeeding in the Quran through reviewing of Albaqarah verse 233 and then correlated to other supporting verses. In general, breastfeeding is a natural activity of woman who has a child. However, the Qur'an sees it as aprivilege for women, rather than a command of Allah. Breastfeeding is also full of benefits for human being. For advanced discussion, the reasons for the order can be scientifically proven havinga lot of beneficial both psychologically and physically for child and mother. Scientific facts show that the composition of breast milk contains the elements needed by the child that not found in others. Thus, it will physically make the child healthy. The breastfeeding process also helps mothers overcome their psychological problems postpartum, and will strengthen the emotional bond to children (bounding attachment).